A Mixed Methods Approach To Prioritizing Components Of Uganda’s ehealth Environment - Mukooyo, Eddie Sefululya; Lutwama, Andrew; Munabi, Ian Guyton; Sewankambo, Nelson; Aceng, Ruth Jane (Pan African Medical Journal, 2015)
Globally the use of information and communication technologies (ICTs) in healthcare, eHealth, is on the increase. This increased use is accompanied with several challenges requiring uniformly understood and accepted regulations. Developing such regulations requires the engagement of all stakeholders. In this manuscript we explored the priorities of various eHealth stakeholders in Uganda to inform the eHealth policy review process.
Keywords: Information and communications technologies, policy, eHealth